The Impact of Progressive Collapsing Foot Deformity on Foot & Ankle Kinematics and Plantar Pressure During Simulated Gait. Issue 1 (January 2022) - Henry, Jensen K.; Hoffman, Jeffrey W.; Kim, Jaeyoung; Steineman, Brett D.; Sturnick, Daniel R.; Demetracopoulos, Constantine A.; Deland, Jonathan T.; Ellis, Scott J.
Category: Basic Sciences/Biologics; Hindfoot Introduction/Purpose: Progressive collapsing foot deformity (PCFD) is a 3-dimensional pathology associated with insufficiency of the posterior tibial tendon (PTT), ligamentous failure, joint malalignment, and aberrant plantar force distribution. Existing knowledge of PCFD consists of static measurements, which provide information about the structure of the foot but none about its function. Cadaveric gait models provide an opportunity to measure motion both at the joints primarily affected in PCFD and the adjacent joints that are at risk for progressive subluxation and arthritis. This study sought to develop a flatfoot model for a robotic gait simulator and quantify gait kinematics and plantar pressure between normal and flatfoot conditions, which we hypothesized would be altered after the creation of a flatfoot deformity model. Methods: Cadaveric specimens were loaded on a 6-degree of freedom robotic gait simulator and the extrinsic tendons were attached to linear motors. Ground reaction forces and muscle forces were optimized utilizing an established iterative process. An 8-camera motion capture system was utilized to calculate joint kinematics using reflective markers attached by k-wires into bone. A plantar pressure mat attached to the force platform was used to calculate the center of pressure excursion index (CPEI) for each condition. The flatfoot model was created via sectioning of the spring ligament and medial talonavicular joint capsule followed by cyclic axial compression until 5-15° of talonavicular abduction was achieved in a static, loaded pose. Testing of the flatfoot state was then performed with inactivation of the PTT. Bias-corrected bootstrapped 95% confidence intervals were constructed from the repeated measures difference between flatfoot and normal conditions. Paired t-tests were used to compare the CPEI between conditions. Results: Twelve mid-tibia cadaveric specimens (mean age 73 years, 8 female) with no prior foot/ankle surgery were used. There were significant differences in kinematics between normal and PCFD conditions at the ankle, subtalar, and talonavicular joints (Figure). There was significantly increased ankle plantar flexion in flatfoot in the first 80% of stance phase. There was significantly greater subtalar eversion in flatfoot compared to normal from 10-90% of stance phase. Talonavicular abduction and eversion were also significantly greater in flatfoot from 10-100% of stance. The CPEI was significantly decreased in the flatfoot condition (Figure), indicating a medialization in center of pressure (p<0.0001). Conclusion: The results from this study support our hypothesis of altered kinematics and plantar pressure after flatfoot deformity creation and corroborate previous biomechanical studies of static alignment in PCFD. Increased talonavicular abduction and subtalar eversion are hallmarks of flatfoot deformity, and increased ankle plantarflexion may represent the plantarflexed position of the talus in PCFD. In addition, plantar pressure was significantly medialized with flatfoot deformity. These findings highlight the utility of the gait simulator as a tool for future study of PCFD, especially for analysis of deformity patterns and the specific effects of individual interventions.